2020
DOI: 10.5606/tr-ent.2020.51523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sphenoid sinus volume and pneumatization type on isolated chronic sphenoid sinusitis (fungi and polyps)

Abstract: Objectives: In this study, we aimed to investigate the association of sphenoid volume and pneumatization type with pathologies, including unilateral isolated chronic sphenoid sinusitis with polyps (ICSSwP) and isolated fungal chronic sphenoid sinusitis (IFCSS). Patients and Methods: A total of 26 patients (15 males, 11 females; mean age 49.9±15.0 years; range, 18 to 80 years) with unilateral isolated sphenoid inflammation, pathologically diagnosed as IFCSS (n=14) or ICSSwP (n=12) between January 2010 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…Isolated fungal chronic sphenoid sinusitis showed an association with a larger SS volume, whereas isolated sphenoid sinusitis with polyps was associated with a smaller SS volume. Considering the results of our study and that of Başer et al [21], the larger volume of the sellar type compared to the conchal and presellar types might be related to FB formation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Isolated fungal chronic sphenoid sinusitis showed an association with a larger SS volume, whereas isolated sphenoid sinusitis with polyps was associated with a smaller SS volume. Considering the results of our study and that of Başer et al [21], the larger volume of the sellar type compared to the conchal and presellar types might be related to FB formation.…”
Section: Discussionsupporting
confidence: 77%
“…The sellar type of the SS was identified as a significant predisposing factor to the presence of unilateral SSFBs in both univariable (OR=10.00; 95% CI, 1.87-53.48; p=0.003), and multivariable analyses (aOR=8.96; 95% CI, 1.27-63.19; p=0.03) (Table 3). Başer et al [21] reported an association between SS volume and pneumatization type with pathologies (fungi and polyps). Their conclusion indicated the absence of a statistically significant difference in pneumatization types between the groups of polyps and fungi.…”
Section: Discussionmentioning
confidence: 99%